KEANEKARAGAMAN JENIS JAMUR MAKROSKOPIS DAN KARAKTER TEMPAT TUMBUHNYA PADA HUTAN RAWA GAMBUT SEKUNDER DI DESA KUALA DUA KABUPATEN KUBU RAYA KALIMANTAN BARAT - Setiorini, Juliati Indah; Astiani, Dwi; Artuti, Hanna (Universitas Tanjungpura, 2018)
The research aimed to describe species diversity of macroscopic mushroom and characteristic of growth on closed, medium and open canopy covered in secondary peatland forest in Kuala Dua village Kabupaten Kubu Raya, West Kalimantan. This research was complished by using purposive sampling technique that was purposively placed at located which found macroscopic mushrooms. The number of plots made was 4 plots in each canopy cover with 5 m x 5 m size. The resulted of the studied found 29 species of macroscopic fungi from 2 divisions and 19 families spread over 3 canopy cover classed. The typed of mushrooms is commonly found in the closed canopy covered is Mycena clavicularis which lives on the litter, while on the medium canopy covered is being found Coltricia parennis that live on dead wood and on the open canopy covered is found Hymenochaete rubiginosa that live on dead wood. Macroscopic mushrooms were found as many as 22 species on dead wood, 1 species on the forest floor and 6 species found on the litter. Viewed from their usefulness, macroscopic mushroom was found 1 type belonging to ektomikoriza, 6 types can be consumed, 3 kinds can be made as souvenir and 19 species was decomposer.Keyword: canopy cover, macroscopic mushroom, secondary peat swamp forest